Cheap Talk in Corporate Climate Commitments - Bingler, Julia Anna,Kraus, Mathias,Leippold, Markus,Webersinke, Nicolas (SSRN, 2022)
Corporate climate disclosures are considered an essential prerequisite to managing climate-related financial risks. At the same time, current disclosures are imprecise, inaccurate, and greenwashing-prone. We introduce a deep learning approach to enable comprehensive climate disclosure analyses by fine-tuning the model. From 14,584 annual reports of the MSCI World index firms from 2010 to 2020, we extract the amount of cheap talk, defined as the share of precise versus imprecise climate commitments. We then test various hypotheses by linking three different climate initiatives, namely the Task Force on Climate-Related Financial Disclosure, the Science-Based Targets Initiative, and the Climate Action 100+, to the economic channels of signaling, credibility, and active engagement. In particular, we ask whether these initiatives decrease cheap talk by disciplining companies in how they define and disclose actionable climate commitments in their annual reports
10.2139/ssrn.3998435
Keywords: Graue Literatur; Arbeitspapier; Corporate climate disclosures; voluntary reporting; commitments; TCFD recommendations; textual analysis; natural language processing